Increasing detection rate of Helicobacter pylori infection in nonvariceal upper gastrointestinal bleeding patients by adding histology to the rapid urease test: An experience from Lampang Hospital - Pankongngam, Charan (Biomedical Sciences and Clinical Medicine, 2017)
Objective To evaluate the detection rate of H. pylori in upper gastrointestinal bleeding (UGIB) patients using the rapid urease test (RUT) alone and in combination with histology. Methods A prospective study of nonvariceal UGIB patients at the Internal Medicine Ward at Lampang Hospital from January to September 2016. Esophagogastroduodenoscopy (EGD) was performed and biopsy samples from the gastric body and the antrum were collected for RUT and histology to detect H. pylori infection. Detection rates with both strategies alone and in combination were compared using exact probability test. Results The detection rate of H. pylori infection was 20.7% with RUT alone, 24.8% with histology alone, and 34.5% with a combination of histology and RUT (p =0.006). Conclusions The detection rate of H. pylori infection among nonvariceal UGIB patients can be increased by adding histology to RUT, especially when RUT is negative. This strategy should be introduced universally to improve overall H. pylori detection rate.